A Survey on Current Practice in the Neurosurgical Management of Preterm Infants with Posthemorrhagic Hydrocephalus in Germany - Mauer, Uwe Max; Unterreithmeir, Luise; Jahn, Arne; Wagner, Wolfgang; Kunz, Ulrich; Schulz, Chris (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2013)
Background and Study Aims Different approaches to the management of preterm infants with posthemorrhagic hydrocephalus (PHH) are described in the literature. Likewise, neurosurgical and pediatric surgical departments in German hospitals use different methods to treat these patients. The aim of this study was therefore to assess the current situation regarding the management of PHH, which is a first and essential step toward the development of standards of practice.Patients and Methods In the second half of 2009, we sent standardized questionnaires to 139 neurosurgical departments (number of returned questionnaires: 98) and 73 pediatric surgical departments (returned questionnaires: 62) to identify the principles of PHH management. Preterm infants with PHH are treated in 61 of the neurosurgical and in 20 of the pediatric surgical departments.Results 43 of the 61 neurosurgical departments and 17 of the 20 pediatric surgical departments providing care for preterm infants with PHH treat less than 10 preterm infants with PHH per year. Reservoir placement is performed as the initial treatment in 48 neurosurgical and in 14 pediatric surgical departments.The criteria for the placement of ventriculoperitoneal shunts and the implantation procedure itself are highly variable. Moreover, the percentage of children who require a CSF shunt after initial treatment for PHH ranges between 5 and 95%.Conclusions In Germany, the type of treatment of infants with PHH differs from institution to institution. Clear and consistent guidelines must be established in an interdisciplinary approach to improve and better coordinate the management of infants with PPH.
Keywords: posthemorrhagic hydrocephalus; shunt; preterm infant; neurosurgery; pediatric surgery